Assessing Community Quality of Health Care. (11th June 2015) - Herrin, Jeph; Kenward, Kevin; Joshi, Maulik S.; Audet, Anne‐Marie J.; Hines, Stephen J.
Abstract : Objective: To determine the agreement of measures of care in different settings—hospitals, nursing homes (NHs), and home health agencies (HHAs)—and identify communities with high‐quality care in all settings. Data Sources/Study Setting: Publicly available quality measures for hospitals, NHs, and HHAs, linked to hospital service areas (HSAs). Study Design: We constructed composite quality measures for hospitals, HHAs, and nursing homes. We used these measures to identify HSAs with exceptionally high‐ or low‐quality of care across all settings, or only high hospital quality, and compared these with respect to sociodemographic and health system factors. Principal Findings: We identified three dimensions of hospital quality, four HHA dimensions, and two NH dimensions; these were poorly correlated across the three care settings. HSAs that ranked high on all dimensions had more general practitioners per capita, and fewer specialists per capita, than HSAs that ranked highly on only the hospital measures. Conclusion: Higher quality hospital, HHA, and NH care are not correlated at the regional level; regions where all dimensions of care are high differ systematically from regions which score well on only hospital measures and from those which score well on none.